Long‐term outcomes of Roux‐en‐Y gastric bypass or sleeve gastrectomy in patients with cirrhosis; before, during or after liver transplantation: A single center's experience. Issue 8 (13th June 2021) - Yemini, Renana; Nesher, Eviatar; Braun, Marius; Cohen, Michal; Carmeli, Idan; Mor, Eytan; Keidar, Andrei
Abstract: Background: The increasing prevalence of morbid obesity (MO) results in parallel growth of obesity‐associated liver diseases necessitating liver transplantation (LT). Objective: To examine the feasibility and safety of Roux‐en‐Y gastric bypass or sleeve gastrectomy in the setting of LT. Methods: This retrospective chart review included the data on all the MO candidates before and after LT who underwent bariatric surgery (BS) in our institution between 04/2013–09/2016. The reported outcomes were weight change and early and late postoperative complications (mean follow‐up: 43 ± 11.1 months). Results: Eighteen MO peri‐LT patients (10 females, 8 males, average age 48 years) were included in the study. Ten had cirrhosis (mean Model of End‐stage Liver Disease [MELD] score of 12.5 ± 6.42), three underwent concurrent LT and BS (mean MELD score 23.7 ± 0.58), and five had LT (mean of 56 months from LT). The mean percentage of total and excess weight loss was 31% and 81%, respectively. Six of the eight patients with type 2 diabetes mellitus became normoglycemic after BS. Three patients sustained perioperative complications. Two cirrhotic patients died 1 and 4.5 years after BS with decompensation. Conclusions: Bariatric surgery appears to effectively address obesity in cirrhotic and LT patients. The surgical risk is higher than that of the regular BS population.